Total extra-peritoneal inguinal hernia repair: experience in a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2023)
Background: Open hernioplasty, a traditional procedure, is practiced for decades all over the world, for inguinal hernia repair and the newer procedure of total extraperitoneal (TEP) inguinal hernia repair is the current trend. Aim of this study was to share the experience of TEP inguinal hernia repair.Methods: This retrospective observational study was done from April, 2012 to March, 2021 at BIRDEM General Hospital, Dhaka, Bangladesh. Patients with inguinal hernia reporting to BIRDEM outpatient department (OPD) were counseled for TEP repair. Those who consented were treated electively with a TEP repair for a unilateral or bilateral hernia defect, either direct or indirect. All procedures were completed with patients under general anaesthesia. Polypropylene mesh was placed in preperitoneal space. Followed up records were noted at one week, one month, one and two years after surgery. Patients’ age, hernia types and locations, complications, length of stay in hospital, return to work and recurrence were noted.Results: Total patients were 118 including one female. Patients were between 22 and 72 years. All of them had primary hernias and 72% of them underwent unilateral repairs. One of the cases required conversion to transabdominal preperitoneal procedure. In five patients (4.2%) intraoperative complication occurred and postoperative courses were complicated in 8 patients (6.7%). Patients were able to resume their daily activities after a mean period of 7 days (3 to 10 days). There was no mortality.Conclusion: In patients with uncomplicated inguinal hernias, TEP is associated with a very low overall risk of serious complications and recurrence with a very good functional outcome. It is equally applicable with bilateral inguinal hernias without added risk.BIRDEM Med J 2023; 13(1): 44-48